2020
DOI: 10.2196/17377
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Acceptance and Compliance in Digital Health Assessments During Pregnancy: Prospective Cohort Study

Abstract: Background Pregnant women are increasingly using mobile apps to access health information during the antenatal period. Therefore, digital health solutions can potentially be used as monitoring instruments during pregnancy. However, a main factor of success is high user engagement. Objective The aim of this study was to analyze engagement and factors influencing compliance in a longitudinal study targeting pregnant women using a digital health app with s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…This research focussed on women from a lower socioeconomic background thereby addressing a gap in the current literature and providing a context-specific examination of user engagement. Health apps may be a useful tool for supporting behaviour change in lower socioeconomic groups (Graham et al , 2016), but differences in engagement are seen by socioeconomic background (Brusniak et al , 2020). It is important to build evidence on how continued engagement may be supported in this population group to support behaviour change and related health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This research focussed on women from a lower socioeconomic background thereby addressing a gap in the current literature and providing a context-specific examination of user engagement. Health apps may be a useful tool for supporting behaviour change in lower socioeconomic groups (Graham et al , 2016), but differences in engagement are seen by socioeconomic background (Brusniak et al , 2020). It is important to build evidence on how continued engagement may be supported in this population group to support behaviour change and related health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We found that very few (10/173, 5.8%) women exited the study early and only 3.5% (6/173) never used the app after enrollment. This compares favorably with a study in Germany, which involved monthly web-based visits and surveys to digitally assess pregnancy-related symptoms and complications (including physical symptoms, depression, and anxiety), in which 7% of the women formally exited the study and 55% overall stopped using the app and made no further contact with the study team [ 43 ]. Thus, initial concerns that there might be a high rate of attrition because of the perceived burden of symptom reporting were not borne out in our pilot study.…”
Section: Discussionmentioning
confidence: 86%
“…This offers a possible explanation for the barriers some women experience when booking appointments during pregnancy. For example, Brusniak et al found that most pregnant women in their study showed low compliance and engagement with digital monitoring (41). Health professionals are aware of this problem.…”
Section: Discussionmentioning
confidence: 92%